Assessment of heavy metal pollution risk in sediments of coastal ecosystems in Vietnam - Nguyen, Thi Mai Luu; Dang, Hoai Nhon; Nguyen, Dac Ve; Nguyen, Van Quan; Duong, Thanh Nghi; Hoang, Thi Chien; Nguyen , Ngoc Anh; Bui, Van Vuong; Nguyen, Duc The; Le , Van Nam; et al. (Vietnam Journal of Marine Science and Technology, 2025)
The grain sizes and heavy metal contents of surface sediments in coastal ecosystems of Vietnam, including estuaries, seagrasses, coastal lagoons, embayments, and coral reefs, were analysed from 43 samples. Heavy metal pollution indices such as geoaccumulation (Igeo), the contamination factor (CF), the enrichment factor (EF), the ecological risk potential (ER), the degree of contamination (CD), and the ecological risk (RI) were used to evaluate sediment quality. The surface sediments were distributed into 9 types: very fine gravel, very coarse sand, coarse sand, medium sand, fine sand, very fine sand, very coarse silt, coarse silt, and medium silt. The average concentrations of Fe, Mn, Zn, Pb, Cu, Cr, V, As, Co, Cd, and Mo were 1,0015.45, 252.83, 67.91, 14.17, 12.27, 13.98, 17.28, 4.00, 5.63, 0.09, and 0.17 mg/kg, respectively, heavy. The Igeo was unpolluted. The CF had low contamination, except for Zn, which had moderate contamination. The EF were moderate (Pb and As) and moderate (Cd and Zn). The ER, CD, and RI indices were low. Although the average pollution indices were low, some areas in estuaries and coastal lagoon ecosystems presented high values. The negative correlation between Md and heavy metals revealed that grain size impacts heavy metal accumulation. The positive correlation between heavy metals revealed that they had a source origin. Factor analysis also revealed that natural sources of heavy metals accounted for 67.99% of the total heavy metals. In addition, heavy metals were also supplied from anthropogenic sources, with Cd and Zn accounting for 13.31% of the total heavy metals. Some areas in estuaries and coastal lagoon ecosystems where Cu, Pb, As, and Zn in sediment exceed the ISQG need to be monitored to monitor the impact and risk to coastal ecosystems.